(untitled) (CIPEEX, 2026)
Introduction: Cervical ectopy is common among women of reproductive age and may cause irregular bleeding, local discomfort, and an increased risk of sexually transmitted infections. Traditional management can delay important interventions, such as intrauterine device (IUD) insertion.Objective: To report the experience of a Women’s Health initiative using low-level laser therapy (LLLT) in the opportunistic management of cervical ectopy, enabling immediate IUD insertion and promoting humanized care.Methodology: This is an experience report conducted with registered nurses during a health initiative, involving clinical assessment and interventions based on updated protocols, while respecting ethics, confidentiality, and patient autonomy.Results and Discussion: The procedure provided symptom relief, reduced inflammation, and allowed for immediate IUD insertion. The experience strengthened professionals’ technical, ethical, and reflective competencies, integrating theory with clinical practice and demonstrating the effectiveness of evidence-based and opportunistic interventions.Conclusion: Opportunistic management with LLLT is safe, effective, and patient-centered, contributing to reproductive health promotion and improving the quality of gynecological nursing care. Keywords: cervical ectopy; low-level laser therapy; IUD insertion; women’s health.